2004
DOI: 10.1556/abot.46.2004.1-2.10
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study ofBetula pendulastands in Hyrcanian forests, North Iran

Abstract: This study was carried out in the rocky forests of Dodangeh, south of Sari, an area extended as a narrow strip from east to west in the heights of Hyrcanian forests, with the area of ca 2,000 ha and the altitude of 2,500-2,950 m a.s.l. Regarding vegetation history, Dodangeh is a refuge for Betula pendula Roth. This species together with Corylus avellana L. are the first ones formed a plant community in Hyrcanian region since the glaciation of the Tertiary period and gradual retrogression of conifers. A number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
3
4
0
Order By: Relevance
“…Acidic situation in group V is responsible for decrease in soil mineralization and then increase the C/N ratio especially in the lower soil depth. Although a low C/N ratio has been recorded in an acidic Hyrcanian forest soil (Ejtehadi et al, 2004), we found that C/N ratios were decreased with an increase in soil pH (Fig. 5) being consistent with findings by Schuster and Diekmann (2005).…”
Section: Article In Presssupporting
confidence: 92%
“…Acidic situation in group V is responsible for decrease in soil mineralization and then increase the C/N ratio especially in the lower soil depth. Although a low C/N ratio has been recorded in an acidic Hyrcanian forest soil (Ejtehadi et al, 2004), we found that C/N ratios were decreased with an increase in soil pH (Fig. 5) being consistent with findings by Schuster and Diekmann (2005).…”
Section: Article In Presssupporting
confidence: 92%
“…Irano–Turanian and Mediterranean). This is consistent with previous studies showing that the upper areas of the Hyrcanian forest benefits much from plants of Euro–Siberian origin (Zohary , Akhani , Ejtehadi et al , Jafari and Akhani , Akhani et al ). Nevertheless, there is a consistent penetration of Irano–Turanian elements into neighboring rocky habitats of the Hyrcanian area (Akhani and Ziegler , Jafari and Akhani ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the most important differences between the two preceding vegetation units are the rocky habitats and the high occurrence of Fagus orientalis in the former. Despite the dominance of Carpinus orientalis communities on rocky outcrops and cliffs of many parts of western, central and eastern parts of lowlands and mountain areas of the Hyrcanian area (Dorostkar and Noirfalise , Akhani and Ziegler , Jafari and Akhani ), the Betula pendula remnant community occurs locally on more or less inaccessible cliffs of the study area and in some rocky forests of Dodangeh, Sari (Ejtehadi et al ). This vegetation type is generally species poor and accompanied by Quercus macranthera, Johereniopsis seseloides, Saxifraga iranica, Asplenium trichomanes and Alchemilla cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations